Assessment on Religious Values and Ethics in the Independent Curriculum - Mardatillah, Ollyvia; Nirwana, Evi Selva (International Journal of Education, Information Technology, and Others, 2024)
This study aims to examine the practice of assessment on the achievement of religious values and ethics of children aged 5-6 years at Witri Kindergarten, Bengkulu City, using a qualitative approach involving literature review and document analysis. The Independent Curriculum is the main focus in understanding how these values are integrated in early childhood learning. The subjects of the study include teachers and principals who are directly involved in the assessment process. The data was collected through in-depth interviews and document analysis, then analyzed thematically. The results of the study show that religious values and ethics have been well integrated in the Independent Curriculum, with a checklist assessment technique. From the assessments that have been carried out, it shows that children's religious values and ethics have reached the development achievements that have been determined in the independent curriculum. The development of religious values and children's ethics is achieved through the application of teachers in following the achievement indicators that have been determined in the curriculum.